Technological Acceptance of Cattle Farmers in Mobile Applications for Livestock Digital Marketing - Triatmojo, Agung; Qui, Nguyen Hoang; El Sayed, Yasser Basstawy; Ummul Muzayyanah, Mujtahidah Anggriani; Syahlani, Suci Paramitasari; Guntoro, Budi (Buletin Peternakan, 2024)
The farmers have encountered challenges in conducting livestock trade due to the absence of dealer activity caused by Anthrax and Foot Mouth Disease (FMD) epidemics. In this context, it is crucial to utilize technology in livestock marketing to obtain current market information from distant marketplaces and reduce the risk of contagion. To meet these purposes, a mobile phone application has been developed in order to be used by cattle farmers; after that, market testing has been conducted to gain feedback and determine the segmentation. Thus, the study aimed to examine the differences in the perceived ease of use, perceived usefulness, and social impact amongst farmers who are willing and unwilling to embrace a mobile phone application for digital marketing. A total of 968 cattle farmers were surveyed with stratified random sampling techniques in the Special Region of Yogyakarta. The data obtained were analyzed using mean difference inferential analysis. The result showed that farmers with various categories of age, education, farm revenue, farmers group, farmer experience, cattle ownership, and regions have significantly different (p<0.01) perceived usefulness (PU), perceived ease of use (PE), and social influence (SI) on mobile applications for livestock digital marketing. Furthermore, farmers willing to adopt mobile application have significantly higher (p<0.01) PU, PE, and SI factors. This study recommends mobile app developers evaluate potential user needs and background factors that may influence farmers' interest.